2014
DOI: 10.1111/1574-6941.12370
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen availability and distance to surface environments determine community composition and abundance of ammonia-oxidizing prokaroytes in two superimposed pristine limestone aquifers in the Hainich region, Germany

Abstract: We followed the abundance and compared the diversity of ammonia-oxidizing archaea (AOA) and bacteria (AOB) in the groundwater of two superimposed pristine limestone aquifers located in the Hainich region (Thuringia, Germany) over 22 months. Groundwater obtained from the upper aquifer (12 m depth) was characterized by low oxygen saturation (0-20%) and low nitrate concentrations (0-20 μM), contrasting with 50-80% oxygen saturation and 40-200 μM nitrate in the lower aquifer (48 m and 88 m depth). Quantitative PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 73 publications
(109 reference statements)
8
26
0
Order By: Relevance
“…Groundwater bacterial 16S rRNA gene numbers, providing an approximation of the total microbial population, ranged from 3.11 ϫ 10 5 to 2.69 ϫ 10 8 genes liter Ϫ1 at the three different sites, as reported previously (44). Archaeal 16S rRNA genes were ϳ2 orders of magnitude less abundant than bacterial 16S rRNA genes, and their numbers ranged from 1.3 ϫ 10 3 to 4.6 ϫ 10 5 genes liter Ϫ1 (44). Similar to the RubisCO-encoding genes, there were strong temporal fluctuations but no significant differences among the three sampling sites.…”
Section: Diversity Of Active Groundwater Bacterial Communities (16s Rsupporting
confidence: 80%
See 1 more Smart Citation
“…Groundwater bacterial 16S rRNA gene numbers, providing an approximation of the total microbial population, ranged from 3.11 ϫ 10 5 to 2.69 ϫ 10 8 genes liter Ϫ1 at the three different sites, as reported previously (44). Archaeal 16S rRNA genes were ϳ2 orders of magnitude less abundant than bacterial 16S rRNA genes, and their numbers ranged from 1.3 ϫ 10 3 to 4.6 ϫ 10 5 genes liter Ϫ1 (44). Similar to the RubisCO-encoding genes, there were strong temporal fluctuations but no significant differences among the three sampling sites.…”
Section: Diversity Of Active Groundwater Bacterial Communities (16s Rsupporting
confidence: 80%
“…Substantial temporal fluctuations of cbbL and cbbM gene abundances of 2 orders of magnitude at each site were observed but without significant differences in the abundances of these genes between the upper and lower aquifers or between the two wells of the lower aquifer. Groundwater bacterial 16S rRNA gene numbers, providing an approximation of the total microbial population, ranged from 3.11 ϫ 10 5 to 2.69 ϫ 10 8 genes liter Ϫ1 at the three different sites, as reported previously (44). Archaeal 16S rRNA genes were ϳ2 orders of magnitude less abundant than bacterial 16S rRNA genes, and their numbers ranged from 1.3 ϫ 10 3 to 4.6 ϫ 10 5 genes liter Ϫ1 (44).…”
Section: Diversity Of Active Groundwater Bacterial Communities (16s Rsupporting
confidence: 76%
“…The prokaryotic population densities are similar in the target aquifers of the two aquifer assemblages, ranging from 2.7 × 10 6 to 3.8 × 10 8 cells L −1 over time (Opitz et al, 2014), which is similar to microbial abundances observed in spring water of alpine karst aquifers (Farnleitner et al, 2005). Quantitative PCR targeting bacterial and archaeal 16S rRNA genes suggested that archaea form a fraction of 0.03-8.2% of the total microbial population across different transect locations.…”
Section: Microbial Communitiessupporting
confidence: 59%
“…DOC and TOC show a relative decrease with presumed flow direction in both assemblages. Microbial processes in the different aquifer assemblages may thus be more important than surface inputs in controlling the amount and composition of DOC and TOC with progressively longer flow distances (Opitz et al, 2014).…”
Section: Hydrogeochemistrymentioning
confidence: 99%
See 1 more Smart Citation